2016
DOI: 10.1002/mdc3.12449
|View full text |Cite
|
Sign up to set email alerts
|

The Corpus Callosum Splenium Sign in Fragile X‐Associated Tremor Ataxia Syndrome

Abstract: Background Hyperintensities in the splenium of the corpus callosum (CCS) have been proposed as a radiographic diagnostic criterion for fragile X‐associated tremor ataxia syndrome (FXTAS). Methods Magnetic resonance images from patients with FXTAS and from nonpremutation carriers with movement disorders were viewed by a radiologist who was blinded to gene status, and radiographic criteria for FXTAS were scored. Phenotypic data used for diagnosis of FXTAS also were collected. Results Twenty‐two patients with FXT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 18 publications
(28 reference statements)
0
15
0
Order By: Relevance
“…Atrophy, white matter changes, and hyperintensities in the splenium of the corpus callosum have also been reported …”
Section: Discussionmentioning
confidence: 99%
“…Atrophy, white matter changes, and hyperintensities in the splenium of the corpus callosum have also been reported …”
Section: Discussionmentioning
confidence: 99%
“…CCS sign is another imaging marker, defined by hyperintensity in the splenium of the corpus callosum. One study reported its sensitivity and specificity in men to be 0.87 and 0.6, respectively (Deborah, Hall, & P, Meghan Hermanson BS, Emily Dunn MD, The, ). In our study, MCP sign was present only in patients with FXTAS.…”
Section: Discussionmentioning
confidence: 99%
“…and in the splenium of the corpus callosum (CCS). [48][49][50][51] White matter lesions in the MCP is a highly specific, 48 but not pathognomonic, MRI finding of FXTAS. This MCP sign is more common among male carriers than female carriers (60 vs. 13%) 50 and associated with more severe cognitive deficits and a longer history of symptoms.…”
Section: Fragile X-associated Primary Ovarian Insufficiencymentioning
confidence: 99%
“…52 While the lesions in MCP are a distinguishing sign of FXTAS, white matter lesions in the CCS seem to provide a higher sensitivity in both male and female carriers, though with lower specificity. 51 A recent study suggested the decrease of middle cerebellar peduncle width as an early radiological change of emerging FXTAS. 53 Although FXTAS has been known for about two decades, it is believed to be underdiagnosed for there is no pathognomonic presentation and the clinical symptoms can mimic or co-occur with other common neurological illnesses such as Parkinson disease or Alzheimer disease.…”
Section: Fragile X-associated Primary Ovarian Insufficiencymentioning
confidence: 99%